Visual Acuity Outcome over Time in Non-Infectious Uveitis. (18th August 2021) - Pistilli, Maxwell; Joffe, Marshall M.; Gangaputra, Sapna S.; Pujari, Siddharth S.; Jabs, Douglas A.; Levy-Clarke, Grace A.; Nussenblatt, Robert B.; Rosenbaum, James T.; Sen, H. Nida; Suhler, Eric B.; Thorne, Jennifer E.; Bhatt, Nirali P.; et al.
ABSTRACT: Introduction : We evaluated visual acuity (VA) over 5 years in a subspecialty noninfectious uveitis population. Methods : Retrospective data from 5, 530 noninfectious uveitis patients with anterior, intermediate, posterior or panuveitis were abstracted by expert reviewers. Mean VA was calculated using inverse probability of censoring weighting to account for losses to follow-up. Results : Patients were a median of 41 years old, 65% female, and 73% white. Initial mean VA was worse among panuveitis (20/84) than posterior (20/64), intermediate (20/47), and anterior (20/37) uveitides. On average, mean VA improved by 0.62, 0.51, 0.37, and 0.26 logMAR-equivalent lines over 2 years, respectively (each P < .001), then remained stable, except posterior uveitis mean VA worsened to initial levels. Conclusion : Mean VA of uveitic eyes improved and, typically, improvement was sustained under uveitis subspecialty care. Because VA tends to improve under tertiary care, mean VA change appears a better outcome for clinical studies than time-to-loss of VA.